REDESIGN VISUAL IDENTTY PRODUK KOPI “YOU COFFEE” WONOSALAM GUNA MENINGKATKAN BRAND AWARENESS - Nurdiansyah, Pungky Gilang; Yurisma, Dhika Yuan; Riqqoh, Abdullah Khoir (Jurnal Art Nouveau, 2019)
inside this document, researchers do an observation on coffee products from “You Coffee” Wonosalam and found a problem, “You Coffee” does not have a visual identity that can describe the characteristics of “You Coffee”. this research will focus on the new logo as a visual identity. The concept for this redesign is Vibrant. The concept is to make an impression to the public and consumer that products of “You Coffee” is the Vibrant product Wonosalam coffee by making a visual identity that can describe the characteristics of “You Coffee”.This redesign also makes the Graphic Standart Manual that provide an explanation for the logo of “You Coffee” brand that included explanation logos concept and application for design execution. implementation of stationery sets, flyer, x-banner, packaging, posters, and merchandise is included as an information media in knowing about “You Coffee” Wonosalam.